Variability and accuracy of multiple saliva pepsin measurements in laryngopharyngeal reflux patients - Jerome R. Lechien; Francois Bobin (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective To study the variability and diagnostic value of multiple salivary pepsin measurements in the detection of laryngopharyngeal reflux (LPR). Methods Patients with LPR symptoms were consecutively recruited from December 2019 to Augustus 2022. Twenty-one asymptomatic individuals completed the study. The diagnostic was confirmed with hypopharyngeal–esophageal impedance-pH monitoring (HEMII-pH). Patients collected three saliva samples during the 24-h testing period. Symptoms and findings were studied with reflux symptom score-12 and reflux sign assessment. Sensitivity, specificity, positive (PPV) and negative (NPV) predictive values of pepsin measurements were calculated considering morning, post-lunch and post-dinner samples. The consistency and relationship between HEMII-pH, pepsin measurements, and clinical features were investigated. Results Morning, post-lunch and post-dinner saliva pepsin concentrations were measured in 42 patients. Pepsin measurements were 64.9%, 59.5%, and 59.0% sensitive for morning, post-lunch and post-dinner collections at cutoff ≥ 16 ng/mL. Considering the highest concentration of the three pepsin saliva collections, the accuracy, sensitivity, specificity and PPV were 70.5%, 73.0%; 66.7% and 78.9%, respectively. Morning pepsin measurements reported higher consistency, sensitivity, and specificity than post-dinner and post-lunch pepsin measurements. Conclusion The collection of several saliva pepsin samples improves the detection rate of LPR. In case of high clinical LPR suspicion and negative pepsin test, a HEMII-pH study could provide further diagnostic information.